MALAY OR ACEHNESE SOVEREIGNTY DURING THE REIGN OF SULTAN ALAUDDIN MANSUR SHAH (1577 - 1585): WESTERN IMPERIALIST BASTION IN THE EAST - Khairul Nizam bin Zainal Badri (Balai Pelestarian Nilai Budaya Sumatera Barat, 2022)
The 16th century had shown that Western powers so vigorously expanded their influence in the East. Their main goal is to spread the mission of Christianization and reap wealth within the Malay world. Aceh is considered the main rival in the East because of its power as the strongest country in the Malay world and its position as a major center of trade routes. The reign of the 8th Sultan of Aceh, Sultan Alauddin Mansur Shah is regarded as a critical period for the Muslims in the East because at that time the Portuguese and the Spanish conspired to conquer the Muslim countries. The situation is causing Sultan Alauddin Mansur Shah to take steps to defend Islam and the sovereignty of the states in the Malay world. This study uses the qualitative method. The archival approach was chosen to examine the documents relevant to the scope discussed. In order for the study to be more structured, the aspect of historiography based on the sequence of events becomes a consideration. To ensure the accuracy of events within the reign of Sultan Alauddin Mansur Shah, the cross-reference technique of information is done. This technique is very important and relevant given that no thorough research has ever been conducted for the reign of Sultan Alauddin Mansur Shah with respect to the scope of the study. The result of the study indicates that Sultan Alauddin Mansur Shah emphasized the understanding of monotheism-Sufism among the community to develop the spirit of jihad against Western colonialists. Apart from that, he also implemented the constitution based on Islamic law. In order for the sovereignty of states in the Malay reserved, he has built good relations with other states of Pahang and Brunei in particular that each has a great influence within Malaya and Borneo.